2018
DOI: 10.1002/aic.16382
|View full text |Cite
|
Sign up to set email alerts
|

Online Monitoring of the Degree of Fill in a Rotating Full‐Flight Screw of a Corotating Twin‐Screw Extruder

Abstract: It is essential to understand the extent of partial filling of the flight screw, the degree of fill, which is an operational variable of the twin-screw extruder (TSE). This article reports the first attempt to measure, in situ, the degree of fill in a rotating full-flight screw using a specialized light-section method for a TSE. The thickness of the resin sticking to the pushing side decreased with increasing rotational speed. The degree of fill is inversely proportional to the rotational speed and proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…However, a more quantitative in‐situ measurement of the resin profile is indispensable because the specific volume of the resin is temperature dependent and the complete profile of the molten resin cannot be estimated from its solid, semicrystallized state. Thus, in‐situ laser light section measurements were developed and employed to determine the resin profile in our previous study 28 . Figure 7 shows the resin profiles of the full‐flight screw (SC‐34/34) observed by the in‐situ laser light measurements at the port indicated in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a more quantitative in‐situ measurement of the resin profile is indispensable because the specific volume of the resin is temperature dependent and the complete profile of the molten resin cannot be estimated from its solid, semicrystallized state. Thus, in‐situ laser light section measurements were developed and employed to determine the resin profile in our previous study 28 . Figure 7 shows the resin profiles of the full‐flight screw (SC‐34/34) observed by the in‐situ laser light measurements at the port indicated in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The experiments conducted in this study were discussed in our previously published paper on the measurements of the degree of fill 28 . The materials and apparatus used to obtain the results provided in this study were as reported in that previous study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest devolatilization efficiency is obtained by the fast screw rotation speed. The fast screw rotation speed gives a low degree of fill [ 14 , 17 ], which implies that less resin fills the screw. As the exposed surface boundary length is the length where the local degree of fill is zero, the low degree of fill increases the exposed surface boundary length, which in turn increases the devolatilization efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The volatile concentration used for the simulation is larger than that used to obtain the experimental result. To understand the cause-and-effect relationship, we determined the resin profile using the laser-light section method, previously developed by our group [ 17 ]. Figure 9 shows that the resin profiles at 120 and 90 rpm agree well with the simulation and experimental results.…”
Section: Resultsmentioning
confidence: 99%